Pembatasan Kekuasaan Amendemen Konstitusi: Teori, Praktik di Beberapa Negara dan Relevansinya di Indonesia - Mohammad Ibrahim (The Constitutional Court of the Republic of Indonesia, 2020)
In comparative constitutional law, the doctrine of unconstitutional constitutional amendments has in recent years attracted wide attention among scholars. The consequence of the doctrine is that there are limits to constitutional amendments. This paper seeks to explore theories that explain how authorities to amend the constitution may be limited. In addition, it also discusses the practice of the doctrine of countries such as Germany, India and Colombia. Drawing from the experiences of these countries, it attempts to answer whether the doctrine can be used in the Indonesian constitutional system. It argues that under the 1945 Indonesian Constitution, there exist unamendable provisions. Therefore, the Constitutional Court might adopt the view that there are limits to constitutional amendments in Indonesia if there was a constitutional amendment to unamendable provisions. This doctrinal legal research uses normative legal and comparative approaches.